Estimate of concrete block texture using image analysis - Felipe, A. S. [UNESP]; Camacho, J. S. [UNESP]; Albuquerque, M. C F [UNESP]; Andolfato, R. P. [UNESP] (My University, 2012)
The texture of concrete blocks is very important and is often the decisive factor when choosing a product, particularly if the building specifications call for high-strength blocks allied to low-cost finish, in which case exposed blocks with a closer texture are often preferred. Furthermore, a closer texture, especially for exteriors, may be a vital factor in ensuring the building's durability. At present, however, there is no standard to quantify the texture of a structural block. Further, when studying masonry blocks compressive strength should never be overlooked. This article discusses a procedure to produce concrete block textures with and without the addition of lime, but still to achieve the required compressive strength. The method used in this study, to evaluate texture, proved to be simpler and cheaper than methods reported by other authors in the literature. The addition of small quantities of lime proved beneficial for both texture and compressive strength. Increasing the amount of lime further, however, only improved texture.
Keywords: Concrete block; Concrete block texture; Image analysis